Genome diversity of Shigella boydii. Issue 4 (6th April 2016) - Kania, Dane A.; Hazen, Tracy H.; Hossain, Anowar; Nataro, James P.; Rasko, David A.
Abstract : Shigella boydii is one of the four Shigella species that causes disease worldwide; however, there are few published studies that examine the genomic variation of this species. This study compares genomes of 72 total isolates; 28 S. boydii from Bangladesh and The Gambia that were recently isolated as part of the Global Enteric Multicenter Study (GEMS), 14 historical S. boydii genomes in the public domain and 30 Escherichia coli and Shigella reference genomes that represent the genomic diversity of these pathogens. This comparative analysis of these 72 genomes identified that the S. boydii isolates separate into three phylogenomic clades, each with specific gene content. Each of the clades contains S. boydii isolates from geographic and temporally distant sources, indicating that the S. boydii isolates from the GEMS are representative of S. boydii. This study describes the genome sequences of a collection of novel S. boydii isolates and provides insight into the diversity of this species in comparison to the E. coli and other Shigella species. Abstract : This comparative genomic study identifies the diversity of Shigella boydii isolates when compared to reference isolates of closely related pathogens. Abstract :